Accuracy of intraoral scanners based on jaw curve and inter-implant distance - Mohialdeen, Hasan Khiraldeen; Abdulla, Mohammed A.; Al-Noori, Ammar Kh.; Mohamad, Ashraf Measar (Dental Journal (Majalah Kedokteran Gigi), 2024)
Background: In digital dentistry, the intraoral scanner (IOS) is the primary data-collecting device. The data must be accurate to prevent undesirable stresses and technological difficulties resulting from prosthetic misfits. The span length of restorations influences the accuracy of IOS impressions. Purpose: This research aimed to compare the accuracy of virtual models scanned by different IOSs to determine whether jaw curvature and inter-implant distance affect accuracy. Methods: Four mandibular edentulous models were prepared by replacing the site of the missing tooth with an implant. The prepared holes were drilled at 7mm, 14mm, 21mm, and 28mm. Five scans for each model were taken with a desktop laboratory scanner as a reference model and with Trios3Shape and 3Disc Heron IOSs to evaluate trueness and precision (T&P). The scans were saved as standard triangulation language files and statistically analyzed at a level of significance (P ≤ 0.05). Results: There was a significant difference between the IOSs in inter-implant distances (P < 0.05). The greatest distortion was reported in the 21mm and 28mm groups for both scanners (P ≤ 0.05), while the lowest distortion was observed in the 7mm and 14mm groups for the Trios3Shape scanner. Conclusion: Jaw curvature and inter-implant distance impacted the accuracy of the IOS. Distortion and reduced reproducibility of T&P increased with jaw curve and inter-implant distance. The Trios3Shape IOS showed maximum accuracy at 7mm and 14mm inter-implant distances, while the 3Disc Heron IOS produced significant distortion of trueness at 21mm and 28mm inter-implant distances.